A Collection of Pseudo-Words to Study Multi-Talker Speech Intelligibility without Shifts of Spatial Attention - Allen, Kachina; Alais, David; Carlile, Simon (Frontiers in Psychology, 2012)
A new collection of pseudo-words was recorded from a single female speaker of American English for use in multi-talker speech intelligibility research. The pseudo-words (known as the PARG collection) consist of three groups of single syllable pseudo-words varying only by the initial phoneme. The PARG method allows speech intelligibility to be studied free of the influence of shifts of spatial attention from one loudspeaker location to another in multi-talker contexts. To achieve this, all PARG pseudo-words share the same concluding rimes, with only the first phoneme serving as a distinguishing identifier. This ensures that listeners are unable to correctly identify the target pseudo-word without hearing the initial phoneme. As the duration of all the initial phonemes are brief, much shorter than the time required to spatially shift attention, the PARG method assesses speech intelligibility without the confound of shifting spatial attention. The PARG collection is available free for research purposes.